2015
DOI: 10.18203/2319-2003.ijbcp20151367
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of L-arginine-induced acute pancreatitis by meloxicam and/or L-carnitine in rats

Abstract: Background: Acute pancreatitis (AP) is an inflammatory disease, where oxidative stress, subsequently inflammatory mediators activation play a pivotal role. Currently, no definite treatment exists and therapy is mainly supportive that directed to inhibit local pancreatic injury and systemic inflammatory complications. This study is presented to explore whether anti-inflammatory and/or antioxidant drug could ameliorate L-arginine-induced AP. Methods: Rats were sub-grouped randomly into five groups. Control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…The current study induced experimental AP in rats by using a single I.P injection of L-arginine in a dose of 250 mg/100g body weight. This is in accordance with El-Rahman et al (2011) [21] and Hasan et al (2015) [22] . L-arginine produces biochemical and histological changes like that of human AP [23] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current study induced experimental AP in rats by using a single I.P injection of L-arginine in a dose of 250 mg/100g body weight. This is in accordance with El-Rahman et al (2011) [21] and Hasan et al (2015) [22] . L-arginine produces biochemical and histological changes like that of human AP [23] .…”
Section: Discussionsupporting
confidence: 92%
“…L-arginine produces biochemical and histological changes like that of human AP [23] . It distorts the membranes of zymogen granules and release their enzymes to the interstitium causing inflammation [22] . Time of scarification was chosen according to Moreira et al, 2011 [24] who stated that peak histological changes were observed around 72 h after induction of AP.…”
Section: Discussionmentioning
confidence: 99%
“…This could result in formation of MDA, which can activate nuclear factor-kappa B (NF-κB) with a subsequent up regulation of various inflammatory cytokines, which has been found by Yenicerioglu et al (2013). Hasan et al (2015) have also reported that the excess ROS could attack lipids and proteins in the membranes of zymogen granules in pancreas which led to infiltration of great amount of digestive enzymes into pancreatic tissues with subsequent autodigestion and elevation of pancreatic enzymes that is in accordance with our study results. Furthermore, Mirmalek et al (2016) have shown that activation of granulocytes and other proinflammatory mediators is regulated by TNF-α, which activates intracellular protease (trypsinogen) and thus cellular necrosis.…”
Section: Discussionsupporting
confidence: 91%
“…An elevated level of NO could be ascribed to induction of iNOS that was evoked by inflammatory cytokines. NO reacts with superoxide anion to form peroxynitrite that can react directly with lipid, protein and DNA resulting in cellular dysfunction and tissue injury what has been demonstrated in many studies (Biradar and Veeresh 2013;Al-Malki 2015;Hasan et al 2015;Aziz et al 2017).…”
Section: Discussionmentioning
confidence: 91%
“…This results in releasing the digestive enzymes, cellular proteins, and increased levels of inflammatory mediators. 5 Honeybees products include numerous substances such as bee venom, bee propolis, bee pollen, and royal jelly. They are known to have many medicinal and health-promoting properties.…”
Section: Introductionmentioning
confidence: 99%